The 1966 International Covenant on Civil and Political Rights (ICCPR) and the UN Human Rights Committee - Karakamisheva-Jovanovska, Tanja (The Universal Protection of Human Rights, 2026)
Abstract: After World War II, the world desperately needed strong faith in humanity, human rights and the values of civilisation. The world needed a strong motive and U-turn towards human solidarity and the rule of law and order, in order to win over the previous elitist arbitrariness and the “rule” of arms. That is why the international community put much of its efforts into drafting the UN Charter, with an aim to reaffirm faith in fundamental human rights, in the dignity and value of the human individual, and in the equal rights of men and women from nations large and small. Historically speaking, civil and political rights protected in the ICCPR enabled the recognition of the human being and its liberties, especially in terms of citizenship rights, the protection of physical integrity, freedom of speech and thought, freedom from torture and slavery, the right to vote, etc. On the other side, the International Covenant on Economic, Social and Cultural Rights (ICESCR) protects the labour rights, the right to an adequate standard of living, the right to good health, the right to education, cultural rights, etc, which are all considered as “debt obligation”. This means that the State has to step up and take appropriate measurements to guarantee their application, contrary to Civil and Political Rights. These two Covenants are well-known as the International Bill of Rights. Prof. John Humphrey prepared the first documented outline of an International Bill of Human Rights covering over 400 pages. The Universal Declaration was constructed upon a firm international basis wherein no regional philosophy or way of life was permitted to prevail. The Declaration was a synthesis, not only of all the hundreds of suggestions that had been made by governments, private organisations, and individuals, but also of the law and legal practices in all the various Members of the United Nations. In this chapter, special emphasis will be placed on the role and importance of the ICCPR in relation to the development of human rights. First the structure of the Covenant will be explained, and then the relationship between this Covenant and René Cassin’s concept will be elaborated. Also, the Covenant will be analysed through a comparative prism with other relevant regional documents, their connection and mutual influence, as well as the monitoring that the UN Human Rights Committee (the Committee) performs in relation to the application of the Covenant. At the end of the chapter, several landmark cases from the work of the Committee will be elaborated upon, as well as relevant cases referring to Central and Eastern European countries.Keywords: UN, ICCPR, ICESCR, Human Rights Committee, René Cassin’s concept